2014
DOI: 10.17221/259/2013-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Alternate partial root-zone drying irrigation improves fruit quality in tomatoes

Abstract: Sun Y., Holm P.E., Liu F., 2014. Alternate partial root-zone drying irrigation improves fruit quality in tomatoes. Hort. Sci. (Prague),.Alternate partial root-zone drying (PRD) irrigation and deficit irrigation (DI) are water-saving irrigation strategies. Here, comparative effects of PRD and DI on fruit quality of tomato (Solanum lycopersicum L.) were investigated. The results showed that the irrigation treatments had no effect on tomato yield but significantly affected several organic and mineral quality attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 32 publications
0
21
1
Order By: Relevance
“…Tomato is tasty and nutritional and constitutes an important source of minerals, vitamins, and antioxidants that are essential for human health ( Sun et al, 2014 ). The quality attributes including fruit firmness (FM), minerals, concentrations of total soluble solids (TSS), sugars, and organic acids (OAs), as well as their ratio determine not only the sweetness and sourness but also the overall flavor intensity of tomato fruits ( Jones and Scott, 1984 ).…”
Section: Introductionmentioning
confidence: 99%
“…Tomato is tasty and nutritional and constitutes an important source of minerals, vitamins, and antioxidants that are essential for human health ( Sun et al, 2014 ). The quality attributes including fruit firmness (FM), minerals, concentrations of total soluble solids (TSS), sugars, and organic acids (OAs), as well as their ratio determine not only the sweetness and sourness but also the overall flavor intensity of tomato fruits ( Jones and Scott, 1984 ).…”
Section: Introductionmentioning
confidence: 99%
“…Cultivation in inert substrate using split-root system into two parts has been adopted to save water and improve the quality of various vegetables, such as tomato (Sun et al, 2014) and pepper (Shao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional furrow irrigation (CFI), alternate furrow irrigation (AFI) maintained same photosynthetic rate (Pn) but with a decreased transpiration rate in grape, meanwhile, AFI increased Vitamin C and decreased titrated acidity of berry [10] . Sun et al [11] indicated that PRD increased fruit juice concentrations of total soluble solid, glucose, fructose and malic acid. Wei et al [12] used carbon isotope discrimination to show that APRI increased water use efficiency of tomato at leaf and yield scales.…”
Section: Introductionmentioning
confidence: 99%